Environmental governance in Kenya: the role of institutions - Katee, Jacqueliyn Philomena (School For Advanced Legal Studies, 2026)
This study centers on a critical research problem namely: how does Kenya approach the question of Environmental Governance(EG) and what roles do the institutions created under the Environmental Management and Co-ordination Act (EMCA) play to facilitate EG in the country? The study is conducted within the context that Kenya's attempts to reform its EG institutional framework under the EMCA have been experiencing numerous challenges. Paitly due to these setbacks, the management of natural resources in the country is apparently stuck in the centralized and sectoral approach inherited from the colonial government. This is notwithstanding the fact that in the past decade the country registered abundant legal and institutional reforms that could easily be utilized to enhance a coordinated and decentralized approach in the management of natural resources. In spite of their perceived promise of Good Environmental Governance (GEG), these reforms are yet to have tangible impact in reality. The present reality is natural resource management that is scattered across sectoral lines and minimal decentralization to the rural areas. This state of affairs presents vital implications for Kenya's environmental future. The study therefore not only analyses the extent to which the EMCA promotes good governance by its institutions, but also provides proposals for strengthening EG in the country.